2004
DOI: 10.1590/s0102-86502004000300004
|View full text |Cite
|
Sign up to set email alerts
|

Terazosin and propranolol as blockers to the deleterious effect of nicotine in a random skin flap, in the rat

Abstract: Terazosin and propranolol as blockers to the deleterious effect of nicotine in a random skin flap, in the rat 1Terazosina e propanolol como bloqueadores do efeito deletério da nicotina em um retalho cutâneo randômico, no rato ______________________________________________________________________ ABSTRACT PURPOSE: To evaluate the effect of Terazosin and Propranolol on the prevention of necrosis induced by nicotine, in a random skin flap. METHODS: This study utilized 32 adult male Wistar-EPM rats divided, at ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…In an attempt to neutralize the harmful effects of nicotine and reduce the areas of flap necrosis several medications were used 19,20 . Desvascularization cranial of the Transverse Rectus Abdominis Myocutaneous flap (TRAM) in rats was a surgical technique used to induce a programmed and intentional tissue ischemia in flaps, making them survive with less blood flow than usual, causing a stimulus of increased internal vascularity, leading to reduced areas of necrosis flap were also used [21][22][23] .…”
Section: Macroscopic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to neutralize the harmful effects of nicotine and reduce the areas of flap necrosis several medications were used 19,20 . Desvascularization cranial of the Transverse Rectus Abdominis Myocutaneous flap (TRAM) in rats was a surgical technique used to induce a programmed and intentional tissue ischemia in flaps, making them survive with less blood flow than usual, causing a stimulus of increased internal vascularity, leading to reduced areas of necrosis flap were also used [21][22][23] .…”
Section: Macroscopic Evaluationmentioning
confidence: 99%
“…The isoxsuprine hydrochloride produces peripheral vasodilation by a direct effect on vascular smooth muscle, primarily within skeletal muscle, with little effect on cutaneous blood flow [9][10][11][12][13] . In an attempt to neutralize the harmful effects of nicotine and reduce the areas of flap necrosis isoxsuprine hydrochloride was used 19,20 . …”
Section: Introductionmentioning
confidence: 99%
“…It was found that the association between the drugs improved clinical response with survival of the flaps, and the authors considered the association as effective in reversing the effects caused by nicotine 21 . The dose of 2mg/kg of nicotine and the subcutaneous administration used in this study were also used to evaluate the effects of terazosin, a neuroreceptor antagonist, and demonstrated their effectiveness in preventing necrosis, but when combined with propranolol, a beta-blocker, the previous protective effect of necrotic reaction was not observed 22 .…”
Section: Dias Groupsmentioning
confidence: 99%
“…Também é possível testar o efeito benéfico de fármacos como a terazocina sobre a circulação desses retalhos. 15 Esse modelo experimental também tem sido utilizado para a avaliação do efeito da Estimulação Elétrica Nervosa Transcutânea (TENS) sobre a viabilidade desse retalho cutâneo randômico. 16 Também existem pesquisas da utilização desse modelo experimental no estudo de alterações bioquímicas seqüenciais do estresse oxidativo sobre o retalho.…”
Section: Modelo Induzidounclassified